FAKTORâFAKTOR YANG MENDORONG MIGRASI DI KECAMATAN SUNGAI RUMBAI KABUPATEN DHARMASRAYA - Gustina, Fina; Rianto, Slamet; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
Migration is moving from one place to another in relation to a variety of reasons. The movement there that is settled, some are temporary and displacement in the form of regular migration of population movement is essentially a reflection of differences in economic growth and development facility evenness between one region and another. Population growth rate of the region will not move toward regions with higher growth rates. Conditions like these that encourage people to look for new areas that are considered suitable and decent life. Thus the development of the city in accordance with the function of the city itself, a center of economy, technology, education, and administrative center of the appeal of the destination. This study aims to determine the factors that drive migration in the Sungai Rumbai District Dharmasraya Region.This research is descriptive. The population in this study is the Head family who migrated in Sungai Rumbai District Dharmasraya Region, amounting to 1,687 households. Samples were taken with a random sampling technique, so that the samples are 85 families who migrate.The research found that: 1) With the availability of agricultural land then encourage people to migrate to the Sungai Rumbai District Dharmasraya Region, this can be seen from land owned by a family that is 83,53 %, (2) With the high wages available at Sungai Rumbai District Dharmasraya Region encourage people to migrate can be seen on occasion that (89,47% ), (3) With the existing jobs in the Sungai Rumbai District Dharmasraya Region encourage people to migrate can be views at the informal employment is (77,65 %), (4) With knowledge or information that is in the Sungai Rumbai District Dharmasraya Region encourage people to migrate to this land, this can be seen in the knowledge that there indistri ( 80.00 % ).